Effects of Experiential and Generative Learning Strategies on Students’ Academic Achievement, Attitude to and Practical Skills in Biology in Oyo State, Nigeria (2015)
Biology is a core science subject offered in Nigerian Senior Secondary Schools (SSS). However, students‘ achievement in the subject in Oyo State is not encouraging, a trend which probably is due to their poor attitude, low practical skills and teacher-centered teaching strategies. Scholars have thus indicated the need for the adoption of active learning instructional strategies to address this deficiency. Literature have documented the effectiveness of these strategies in enhancing students‘ learning outcomes in Physics and Chemistry but no such studies have been carried out on students‘ achievement in Biology. This study, therefore, determined the effects of Experiential Learning (ELS) and Generative Learning (GLS) Strategies on students‘ academic achievement, attitude to and practical skills in Biology in Oke-Ogun area of Oyo State. The moderating effects of gender and mental ability were also examined. The study adopted pretest-posttest control group, quasi-experimental design with a 3x2x3 factorial matrix. Random sampling was used in selecting three Local Government Areas (LGAs) from Oke-Ogun area of Oyo State. Purposive sampling was used to select nine SSS across the LGAs while an intact class of Senior Secondary Students I was selected from each of the schools for a total of 428 participants. Participants were randomised to ELS, GLS and Control groups, while the treatment lasted 12 weeks. Seven instruments were used: Biology Achievement Test (r=0.74), Students Attitude to Biology Questionnaire (r=0.82), Biology Student Skills Rating Scale (r=0.74), Mental Ability Test (r=0.86) and Instructional guides on ELS (π=0.75), GLS (π=0.78) and control (π=0.76). Seven null hypotheses were tested at 0.05 level of significance. Data were subjected to analysis of covariance, multiple classification analysis and Scheffe post-hoc test. Results showed that treatment had a significant main effect on students‘ achievement score (F(2,410)=522.20,ᶯ2= 0.07) and practical skills(F(2,410)=1299.30,ᶯ2= 0.86) but not on attitude. Participants in ELS had highest achievement scores (=20.14), followed by those in GLS (=17.69) and control (=5.59). Also participants in ELS had the highest enhanced practical skills (=22.56) than those in GLS (=19.66) and control (=9.58). There was a significant main effect of mental ability on students‘ academic achievement in Biology (F(2,410) =5.6, ᶯ2=0.22) but not on gender. Students with high mental ability had higher adjusted mean score (=17.55) than those with low mental ability (=13.60). The two-way interaction effects of treatment and mental ability on students‘ achievement, attitude to and practical skills was not significant. The two-way interaction effects of treatment and gender on students‘ achievement, attitude to and practical skills was not significant. The three-way interaction effect of treatment, gender and mental ability on students‘ achievement, attitude to and practical skills was not significant. The experiential and generative learning strategies enhanced students‘ achievement and practical skills in Biology in Oke-Ogun area of Oyo State. The two strategies should therefore be adopted in teaching Biology to senior secondary school students.